Work Experience and Work Environment as Determinants of Teacher Labor Supply: Evidence from Private High Schools in Jambi City - Kuswanto Kuswanto; Resty Nopya Safitri; Refnida Refnida; Syadiyah Abdul Shukor (Universitas Sarjanawiyata Tamansiswa, 2026)
Unlike previous studies that generally focus on the labor market in general, this study specifically examines the supply of teacher labor in private schools by emphasizing the interaction between experience and the work environment. This study aims to analyze the influence of work experience and the work environment on the supply of private high school teachers in Jambi City. Using a quantitative approach with an ex post facto design, data were collected through questionnaires from 94 respondents and analyzed using multiple linear regression. The results show that experience and the work environment simultaneously have a positive and significant effect on labor supply, with an ability to explain 42.2% of the data variation (R2 = 0.422). Partially, the work environment is proven to have a much stronger influence (coefficient = 2.816) compared to work experience (coefficient = 0.100), making it the most dominant determinant. This finding has important implications for private school management: amidst limited financial structures, creating a supportive and collaborative work climate is the most crucial non-monetary strategy to increase dedication and maintain the supply of quality educators.